EDUCATIONAL PUBLIC POLICIES AND DEMOCRACY IN THE BRAZILIAN POLITICAL SCENARIO - De Assis Lourenco, Flavia Oliveira [UNESP]; Gomes, Fernanda Goncalves [UNESP]; Mattar Damiance, Patricia Ribeiro [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
This manuscript will analyze the relationship, not always explicit, between public educational policies and democracy, in order to reflect the understanding of the relationship in contemporary education and in the consolidation of the democratic state in Brazil. It is a narrative or critical review of the literature, structured in two parts. The first part is based on a synthesis of the role of the State in the conception and execution of educational policies and on the idea of thinking public policies ontologically. The second part is based on movements of reverberation, contextualization, generalization and synthesis of the discourse of the political scientist Yascha Mounk.
Keywords: Public policies; Education; Democracy; Policy